Regional Relative Price Disparities and Their Driving Forces - Eu Joon Chang; Young Se Kim (East Asian Economic Review (EAER), 2017)
This paper studies the long-run behavior of relative price dispersion among cities in Korea with a special emphasis on heterogeneous transitional patterns of price level dynamics. Formal statistical tests indicate considerable evidence for rejecting the null of relative price level convergence among the majority of cities over the sample period of 1985-2015. The analysis of gravity model suggests that the effect of transportation costs on intercity price level differentials is limited, while other socioeconomic factors, such as income, input factor prices, demographic structure, and housing price growth, play key roles in accounting for persistent regional price level disparities. Individual price levels are found to be better explained by a multiple-component model, and the deviations from PPP may be attributed to distinct stochastic common trends that are characterized by income and demographic structure.
Keywords: C38; E31; F22; 330; Relative Price Convergence; Purchasing Power Parity; Heterogeneous Transition; Factor Model; Multiple Stochastic Trends